A Multiyear Survey and Identification of Pepper- and Tomato-Infecting Viruses in Yunnan Province, China - Li, Yueyue; Tan, Guanlin; Xiao, Long; Zhou, Wenpeng; Lan, Pingxiu; Chen, Xiaojiao; Liu, Yong; Li, Ruhui; Li, Fan (Frontiers in Microbiology, 2021)
During pepper and tomato production seasons in 2013–2017, large-scale virus disease surveys were conducted in different regions of Yunnan Province, China. A total of 1,267 pepper and tomato samples with various virus-like symptoms were collected and analyzed for virus infections through dot enzyme-linked immunosorbent assay (dot-ELISA), polymerase chain reaction (PCR), and reverse-transcription (RT)-PCR. The detection results showed that 19 different viruses were present in about 50.9% of the assayed samples, and among these viruses, seven viruses were found in both pepper and tomato samples. Mixed infections with two to three of the 15 identified mixed infection types were found in the pepper samples and 10 identified mixed infection types were found in the tomato samples. Among the infected samples, Tomato spotted wilt orthotospovirus (TSWV) was the most common virus, with a detection rate of about 20.0% followed by Pepper vein yellows virus (PeVYV, 13.0%). This survey revealed for the first time that pepper is a natural host of Tobacco vein distorting virus (TVDV) worldwide and tomato is a natural host of Potato leafroll virus (PLRV) in China. PeVYV, Tobacco mild green mosaic virus (TMGMV) and Wild tomato mosaic virus (WTMV) were first time found in pepper and Tomato mottle mosaic virus (ToMMV) and Chilli veinal mottle virus (ChiVMV) were first time found in tomato in Yunnan Province. Finally, the virus incidences were higher in Kunming, Yuxi, Chuxiong, and Honghe region than other regions.